The nutritional environment and food access of female athletes at HBCUs: a qualitative analysis - Uriegas, Nancy A.; Winkelmann, Zachary K.; Emerson, Dawn M.; Torres-McGehee, Toni M. (Frontiers in Nutrition, 2026)
PurposeFemale student-athletes attending Historically Black Colleges and Universities (HBCUs) may encounter distinct challenges related to food access, particularly when their campuses are situated in areas with limited food availability. This study assessed food security (FS) and explored the lived experiences of HBCU female student-athletes regarding their food environments and access to nutrition.MethodsThis qualitative study used a semi-structured interview protocol derived from quantitative data. Participants were 10 HBCU female athletes (age = 19 ± 1 years) living in on-campus dormitories; recruited after completing a quantitative study examining energy needs. The three-part semi-structured interview protocol included questions about personal experiences surrounding food access and the U.S. Department of Agriculture Six-Item Short Form of the Food Security Survey Module. Interviews were recorded and transcribed verbatim. Three coders analyzed data using the consensual qualitative research tradition. Trustworthiness was established using member checking, multi-analyst triangulation, and external auditing.ResultsFS status was evenly distributed among participants (five food secure, five food insecure). Four domains emerged: (1) on-campus living, (2) personal factors, (3) convenience, and (4) nutritional awareness. Participants described navigating limited cooking resources, inconsistent cafeteria offerings, and time constraints that influenced their food choices. While food sources were available both on and off campus, many participants expressed that these options did not consistently align with their preferences or nutritional needs. Reflections on dietary habits revealed varying levels of nutritional awareness and a desire for more tailored guidance.ConclusionThe findings suggest that while food options exist within HBCU campuses and surrounding communities, they may not fully support the unique needs of female student-athletes. Institutional stakeholders, including administrators, athletic trainers, and coaches, may consider collaborative efforts to enhance food access and nutritional support. This could include increasing awareness of community resources (e.g., SNAP, food banks), revisiting dormitory policies related to cooking, and expanding access to nutrition education. These insights underscore the importance of contextually responsive strategies to promote student-athlete well-being.